2014
DOI: 10.1080/10402004.2014.881581
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Shear Rate, Temperature, and Particle Concentration on the Rheological Properties of ZnO and ZrO2Nanofluids

Abstract: The rheological behavior of ZnO and ZrO 2 nanoparticle suspensions in a polyalphaolefin (PAO 6) was investigated at high shear rates. Nanoparticles were dispersed at 0.5, 1.0, and 2.0 wt% in PAO 6 using an ultrasonic probe to produce nanofluids whose viscosity was determined over shear rates and temperatures ranging from 10 6 to 10 7 s −1 and 40 to 100 • C, respectively. For the particle concentrations tested, the nanofluids exhibited a shear-thinning rheological behavior. The classical models typically used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…For example, the nanolubricants of Hernandez Battez et al (2014) were Newtonian for shear rates less than 700 s −1 and non-Newtonian for significantly larger shear rates (10 6 s −1 to 10 7 s −1 ). Conversely, all of Tseng and Lin (2003) water-based nanofluids exhibited non-Newtonian behavior for shear rates less than 700 s −1 and one of them showed Newtonian behavior for shear rates larger than 700 s −1 .…”
Section: Property Measurementsmentioning
confidence: 99%
“…For example, the nanolubricants of Hernandez Battez et al (2014) were Newtonian for shear rates less than 700 s −1 and non-Newtonian for significantly larger shear rates (10 6 s −1 to 10 7 s −1 ). Conversely, all of Tseng and Lin (2003) water-based nanofluids exhibited non-Newtonian behavior for shear rates less than 700 s −1 and one of them showed Newtonian behavior for shear rates larger than 700 s −1 .…”
Section: Property Measurementsmentioning
confidence: 99%
“…Nanoparticles are responsible for increasing the thermal conductivity of base fluid because of its size which is generally in the extent of 1 to 100 nm 13 . The nanoparticles dispersion in the base oil is termed as Nanofluid 14 . Most of the literature was focused on the use of oxide‐based nanoparticles such as aluminium oxide (Al 2 O 3 ), copper oxide (CuO), and titanium oxide (TiO 2 ) due to their increasing combustion efficiency characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it can be concluded that both methods (listed above) are classical and have their own defects (the addition of dispersant or usage of surfactant into base oil) for solving the oil solubility of TiO 2 nanoparticles. This claim is strengthened by the works of several researchers [3,[8][9][10][11]23,24,[36][37][38]. Therefore, the application process of the two classical methods was named the traditional process (TP).…”
Section: Introductionmentioning
confidence: 95%
“…The use of nanoparticles as oil additives and lubricants is a recent idea. Numerous nanoparticles have been investigated in recent years [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. These oil additives contain small particles of solid material, and their use is not straightforward and only recently has been recognized as feasible.…”
Section: Introductionmentioning
confidence: 99%